2005
DOI: 10.1021/ic0485209
|View full text |Cite
|
Sign up to set email alerts
|

Copper Hydroxydiphosphate with a One-Dimensional Arrangement of Copper Polyhedra:  Cu3[P2O6OH]2

Abstract: A new copper hydroxydiphosphate Cu3(P2O6OH)2 was synthesized, by soft chemistry. The crystal structure was solved ab initio from X-ray powder diffraction data in the triclinic space group P. The structure is built up from [Cu3O10]infinity zigzag chains linked by P2O6(OH) groups to form a tridimensional framework. The [Cu3O10]infinity chains consist of edge-sharing polyhedra. The structure contains two sorts of copper polyhedra: one CuO6 octahedron and two CuO5 pyramids. Magnetization measurements confirm the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…From Table , one can find that the theoretical structure parameters, such as the CuCu bond lengths and the CuOCu angles are in good agreement with the experimental data . In addition, the optimized bond length between Cu(1) and its six O ligands has been measured and is consistent with previous experimental values . It is found that the Cu(1) normalO6 is strongly elongated with two long apical CuO bonds of 2.393 Å along z axis, whereas in the basal plane, the CuO bonds ranging from 1.977Å to 1.996 Å.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…From Table , one can find that the theoretical structure parameters, such as the CuCu bond lengths and the CuOCu angles are in good agreement with the experimental data . In addition, the optimized bond length between Cu(1) and its six O ligands has been measured and is consistent with previous experimental values . It is found that the Cu(1) normalO6 is strongly elongated with two long apical CuO bonds of 2.393 Å along z axis, whereas in the basal plane, the CuO bonds ranging from 1.977Å to 1.996 Å.…”
Section: Resultssupporting
confidence: 81%
“…It was reported that the copper hydroxydiphosphate Cu3(normalP2normalO6OH)2 has a triclinic lattice with space group P true1¯ (No.2) . The lattice constants of this compound at room temperature are a=4.78191(6), b=7.03699(8), c=8.35740(8)Å, α=66.6790(6), β=76.9930(7), and γ=72.0642(6)° . The schematic crystal structure of Cu3(normalP2normalO6OH)2 is depicted in Figure a.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of Mn and Zn, a Wolframite-based MMoO 4 structure is stabilized. Unlike other metal ions, copper(ii) ions tend to form polymeric chains [36][37][38] at around this pH, and these readily react with MoO 4 2-ions to give Lindgrenite (3). However, hydrothermal treatment of ammonium heptamolybdate with copper(ii) ions in the absence of 2-ampy results in ammonium-intercalated hexagonal molybdates.…”
Section: Chemistry Of the Formation Of Molybdates By Hydrothermal Trementioning
confidence: 99%
“…Copper can accommodate various coordinations from tetrahedral or square to pyramidal and octahedral. Thirteen different structures of copper phosphates or hydroxyphosphates have been discovered to date [17]. It is well accepted that there is a close relationship between the morphology and their properties of inorganic materials, that is, morphologies determine their properties since the crystal shape dictates the interfacial atomic arrangement of the material [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%